Emergent and robust ferromagnetic-insulating state in highly strained ferroelastic LaCoO3 thin films - Li, Dong; Wang, Hongguang; Li, Kaifeng; Zhu, Bonan; Jiang, Kai; Backes, Dirk; Veiga, Larissa S. I.; Shi, Jueli; Roy, Pinku; Xiao, Ming; Chen, Aiping; Jia, Quanxi; et al. (Nature communications, 2023)
Transition metal oxides are promising candidates for the next generation of spintronic devices due to their fascinating properties that can be effectively engineered by strain, defects, and microstructure. An excellent example can be found in ferroelastic LaCoO 3 with paramagnetism in bulk. In contrast, unexpected ferromagnetism is observed in tensile-strained LaCoO 3 films, however, its origin remains controversial. Here we simultaneously reveal the formation of ordered oxygen vacancies and previously unreported long-range suppression of CoO 6 octahedral rotations throughout LaCoO 3 films. Supported by density functional theory calculations, we find that the strong modification of Co 3 d -O 2 p hybridization associated with the increase of both Co-O-Co bond angle and Co-O bond length weakens the crystal-field splitting and facilitates an ordered high-spin state of Co ions, inducing an emergent ferromagnetic-insulating state. Our work provides unique insights into underlying mechanisms driving the ferromagnetic-insulating state in tensile-strained ferroelastic LaCoO 3 films while suggesting potential applications toward low-power spintronic devices. Transition metal oxides are a promising class of materials to engineer multiferroic properties for next-generation spintronic devices. Here, the authors demonstrate an emergent and robust ferromagnetic-insulating state in ferroelastic LaCoO 3 epitaxial films by strain-defect-microstructure manipulated electronic and magnetic states.